Hydatid disease: imaging, treatment, and beyond - Baykan, A. H.; Aydin, E.; Koc, M.; Sahin, H.; Karul, A.; Baykan, M. E.; Erturk, S. M. (W B Saunders Co Ltd, 2025)
Hydatidosis is an endemic parasitic disease that can occur in almost any part of the body. It presents in two different forms according to the type of tapeworm: Echinococcus granulosus (hydatid disease [HD]) and Echinococcus multilocularis (alveolar HD). Radiological imaging can reveal the type of cyst, disease activity and progression, and complications, with features depending on the HD stage, the organ involved, and complications. Radiological imaging is also used to plan treatment strategies and evaluate patients at follow-up. Here, we review the morphologies of different HD presentations and their radiological features, the diagnostic findings that suggest possible HD in rare sites, and the potential complications of HD. We also discuss the role of radiology in hydatidosis diagnosis and treatment. (c) 2024 The Royal College of Radiologists. Published by Elsevier Ltd. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Echinococcus-Granulosus; Computed-Tomography; Adrenal-Gland; Rare Cause; Cyst; Diagnosis; Spleen; Ct